(untitled) (Tempo e Argumento, 2021)
Based on reflections by authors like Andreas Huyssen, Maria Angélica Melendi, Paola Helena Acosta Sierra, and Diana Taylor, this article discusses some modes of intervention in the public space that, contemporarily, deal with memory (quite especially, traumatic memory) and resort to expressive effects or performative acts that, in turn, interconnect poetics and policies. The project “Reviving/Reviewing Migrations” is examined in detail, a Brazilian experience in the education area that, inspired by a photographic exhibition by Sebastião Salgado, has been proposing for 2 decades creative and renovating qualification paths, based on fieldwork and, quite especially, on 2 performative acts: photographing and hiking. An experience that interconnects performing and educating, as well as the intense production of memory vectors (such as photographic documentary records) in association with incorporated (collective and individual) memory dimensions. Keywords: memory; photography; hiking; Sebastião Salgado; education.